Unjust Enrichment. : the Comparative Legal History of the Law of Restitution. - Schrage, E. J. H. (Comparative Studies in Continental and Anglo-American Legal History - Band 15., 2013)
Hauptbeschreibung "" ... to be consulted before any significant legal debate."" W.J. Stewart in: Scots Law Times 1995This volume is concerned with the history of the concept of, or of the remedies for, unjust enrichment in the Civil law and the Common law. But this history is radically different in the two systems - different both in the starting point of each system and in the methods by which progress from that starting point was made. What for the Civil law is the starting point is for the Common law the ultimate outcome. The Civil law from its earliest medieval beginnings had before.